Proposta de intervenção urbanística na cidade de Benevides - PA: padronização de calçadas do Centro Comercial - POMPEU, Francilene das Graças Coelho (2022)
Walking is the oldest and most recurrent means of transportation in the world, besides being a healthy habit. Despite this, people walk less and less because the sidewalks, roads through which people walk, are real obstacles, especially for the elderly and people with disabilities. The quality of sidewalks can be enhanced, not only to attract more pedestrians, but also to become a pleasant space, where people want to be and live together. Within this problem, the present work aimed to identify mobility problems on sidewalks in the city of Benevides, located in the Metropolitan Region of Belém, in the state of Pará more precisely in the commercial center of the city, specifically around the municipal market and ancient bus station. For the site, an urban intervention project was elaborated using geoprocessing techniques as an aid in obtaining information about urban space, and propose changes in the direction of construction and adequacy of standardized sidewalks to favor mobility.